2018
DOI: 10.1088/1741-4326/aaf20c
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and correction of the 1/1 error field in Wendelstein 7-X

Abstract: In this paper, vacuum flux surface mapping is used to measure the 1/1 error field in Wendelstein 7-X. Two methods for discriminating the 1/1 perturbation from other co-resonant modes are applied: measurements of the helical axis shift in a magnetic configuration with the rotational transform barely above one on the axis; and measurements of the edge island structure with cancellation of intrinsic 5/5 islands by divertor control coils. The normalized radial 1/1 amplitude in Boozer coordinates is found to be abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 29 publications
4
45
0
Order By: Relevance
“…The selected plasma discharges are in the standard magnetic configuration, with similar parameters (line integrated density of 7 • 10 19 m −2 , input power of 4 MW of ECRH, electron temperature in the core of ∼3 keV), without (experiment #20181010.17) and with (experiment #20181010.18) control coils, which are components designed to induce changes of the island structure. In the latter program, a positive current of 2 kA has been applied to all 10 control coils which results in an increase of the radial component of the magnetic field, increasing the island size while decreasing the connection lengths to the divertors [33,40]. The modification of the SOL geometry translates in an effect on the flows, without modifying the number of islands crossed by the CIS lines of sight.…”
Section: Diagnostic Comparisonmentioning
confidence: 99%
“…The selected plasma discharges are in the standard magnetic configuration, with similar parameters (line integrated density of 7 • 10 19 m −2 , input power of 4 MW of ECRH, electron temperature in the core of ∼3 keV), without (experiment #20181010.17) and with (experiment #20181010.18) control coils, which are components designed to induce changes of the island structure. In the latter program, a positive current of 2 kA has been applied to all 10 control coils which results in an increase of the radial component of the magnetic field, increasing the island size while decreasing the connection lengths to the divertors [33,40]. The modification of the SOL geometry translates in an effect on the flows, without modifying the number of islands crossed by the CIS lines of sight.…”
Section: Diagnostic Comparisonmentioning
confidence: 99%
“…The good correspondence between the measured heat fluxes and the Poincare plots indicate that the W7-X magnetic field is reasonably close to the ideal (no error field) stellarator symmetric magnetic field topology [15,16]. This correspondence can be further explored by comparing the fluxes to a simple field line diffusion model as implemented in the DIV3D code [1], which was used to design the scraper element and is similar to methods used to design the other W7-X divertor components.…”
Section: Comparison To Field Line Diffusion Calculationsmentioning
confidence: 68%
“…Thus the influence of error fields on these measurements could be substantial. In particular the presence of both n/m = 1/1 and n/m = 2/2 magnetic error fields, and their effect on the island divertor have been well documented [15,7]. [20]) associated with outgassing of the divertor but did not appear to affect heat fluxes to the divertor.…”
Section: Flux Surface Measurementmentioning
confidence: 99%
“…field was also demonstrated to be correctible using less than 10% of the rated maximum current capacity of the trim coils [7,14,15]. However, during divertor operation an anomalous interaction between the plasma and carbon tiled wall elements suggested that the edge island chain was not optimally located.…”
Section: Introductionmentioning
confidence: 99%